Assessment of rational prescribing practice among interns: a questionnaire based observational study - Gupta, Rohini; Malhotra, Apoorva; Malhotra, Pavan (International Journal of Research in Medical Sciences, 2018)
Background: Rational use of medicines (RUM) is recognized as an important factor in health policy. Prescribing appropriate drugs in right doses is an integral part by which a physician can influence the patient’s health and well‑being. Rational prescription writing is a skill which should be mastered at the earliest. Understanding the knowledge and perception of interns will help us to identify the problems in clinical pharmacology teaching, and the method to implement RUM. Objective was to assess the rational prescribing practice among interns in a tertiary care teaching hospital. Methods: This cross-sectional, questionnaire-based study was carried out in 92 interns of Acharaya Shri Chander College of Medical Sciences and H, Sidhra, Jammu (J and K). Interns posted in different departments of the hospital in the year 2016 (n = 92) were approached and explained the purpose of the study. 88 gave consent to participate in the study. Out of 88 only, 82 duly filled questionnaires were used for final analysis. Those who were not willing to participate in the study and those whose questionnaires were not duly filled were excluded from the study. The completed questionnaires were then assessed for responses of the students on principles of good prescribing. Results: Of the 92 interns, 88 gave consent to participate in the study while 82 of them returned the duly completed questionnaires (response rate was 89.1%). The mean age of the respondents was 24.1 years. Out of 82 interns, 95.1% respondents were aware about the term RUM, only 8.5% had National List of Essential Medicines of India (NLEMI) available at their work place. Though 41.5% interns were aware of the term P-drug, only 3.7% were aware about STEP criteria. Majority of interns 62.1% relied on information from standard text books whereas 24.3% rely on Medical representatives (MR) for obtaining information about various drugs and regimens. Conclusions: In conclusion, it is encouraging finding that higher percentages of interns were aware about essential medicines (EM) and also prescribe it. However, level of understanding related to personal drug (P-drug) concept and existence of Essential medicine list (EML) are much below par. Furthermore, prescribing by trade name and dependency on MR for drug information is the matter of concern. Hence, there is a need to strengthen the mechanism for continuing professional development of interns to update their knowledge and skills to prescribe rationally.